Mass-Charge and Energy Spectra of Oxygen Ions in a Two-Element Laser-Produced Plasma. (14th February 2008) - Khaydarov, R. T.; Kunishev, U. S.
Abstract : Using a static mass spectrometer, we study the characteristics of multicharge plasma ions generated from solid targets under the action of a 15 nanosecond Nd:YAG laser radiation with maximal intensity10 11  W/cm 2 . We consider two-element solid targets with a mass of the heavy component ranging from 44.9 (Sc) to 174.9 (Lu) with main attention to the properties of oxygen ions. The time-of-flight measurements show that oxygen ions are obtained in the range of the energyE = 40–250 eV with maximal chargeZ max = 2 . The latter is independent on the target composition for the given intensity of the laser radiation. However, the properties of the energy spectra of oxygen ions strongly depend on the second component of the target, which is explained by the interaction between the light and heavy elements of the target.